Service models of the cloud-based learning environment of the educational institution - Mariya P. Shyshkina (Academy of Cognitive and Natural Sciences, 2018)
The article is devoted to creating and development of the cloud based educational and scientific environment of higher education institutions, using modern approaches to the ICT infrastructure design, based on the different types of service models, including public, corporate or hybrid clouds. Object of the study: to conduct the theoretical analysis of the research trends of the cloud based higher education institution ICT infrastructure modeling in the context of the tendencies of the ICT development and standardization. Object of the study: the process of formation and development of the educational and research environment in the higher education institution. The purpose of the article: to reveal the current trends of the cloud-based service models of the learning environment design and implementation. The methods of the study: The analysis of scientific and educational literature on pro-research problems; domestic and foreign experience on the emerging ICT implementation in the learning process. Results: The main types of the service models of design and deploy the cloud-based infrastructure of the educational institution are revealed; the advantages and disadvantages of the cloud-based approach are considered; the promising ways of implementation are considered. Conclusions: there are promising ways of the learning environment cloud-based service models design and application, taking into consideration its preferences and disadvantages for the certain case study.